Antimicrobial Effectiveness Test of Ethanol Extract of Red Betel (Piper crocatum Ruiz And Pav) - Rismahara Lubis; Dodoh Khodijah; Adhisty Nurpermatasari (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Red betel leaf (Piper crocatum Ruiz & Pav) is a traditional medicinal plant that contains active compounds such as flavonoids, alkaloids, tannins, saponins, and essential oils that have potential as antimicrobials. Objective: This study aims to determine the effectiveness of ethanol extract of red betel against microbial growth. Methods: The research was conducted experimentally using the disc diffusion method on agar media with concentrations of 80%, 90% and 100%. The dependent variable was microbial inhibition. Several antibiotics and antifungals were used as positive controls, while distilled water was used as negative control. Results: The results showed that the average inhibition zone against Staphylococcus aureus at concentrations of 80%, 90% and 100% were 26,96 mm, 28,69 mm and 30,1 mm respectively with a positive control of tetracycline of 28.1 mm. In Escherichia coli it was 12,66 mm, 14,13 mm and 15,17 mm respectively with positive control of amoxicillin of 22.16 mm. Pseudomonas aeruginosa produced inhibition zones of 12,7 mm, 14,5 mm and 15,78 mm respectively with a positive control of chloramphenicol of 6.95 mm. In Klebsiella pneumoniae it was 13,47 mm, 14,81 mm and 16,05 mm respectively with ampicillin positive control of 6,22 mm. On Candida albicans, the zones of inhibition were 9,77 mm, 11,26 mm and 12,32 mm, respectively, with a positive control of ketoconazole of 29.95 mm. The zones of inhibition of antibiotics and comparative antifungals varied, some producing larger diameters than the extract, while others were lower. The negative control showed no inhibitory activity. Conclusion: It was concluded that the ethanol extract of red betel was able to inhibit some microbial growth according to the Indonesian Pharmacopoeia VI Edition standard of 14-16 mm.